2008
DOI: 10.1253/circj.72.482
|View full text |Cite
|
Sign up to set email alerts
|

High Intravascular Pressure Attenuates Vascular Dilation Responses of Small Mesenteric Arteries in the Rat

Abstract: revious studies have demonstrated that hypertension and cardiovascular diseases are associated with functional and morphological changes in arteries. [1][2][3] In hypertension, the small arteries and arterioles that determine peripheral resistance undergo changes such as increased reactivity to contractile agents, impaired endothelial function, and vascular smooth muscle growth. 4,5 Although it is unclear whether these are primary or secondary abnormalities, it is plausible that the increased intravascular pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
2
5
1
Order By: Relevance
“…The explanation for this phenomenon is that vasoconstriction induced by a low concentration is an insufficient stimulus to promote the EDRF release process, while the endothelium is unable to overwhelm higher concentration-induced vasoconstriction. This notion is supported by the report by Gündüz et al (22) that high intravascular pressure impairs both endothelium-dependent and independent dilation of rat small mesenteric arteries.…”
Section: Discussionsupporting
confidence: 63%
“…The explanation for this phenomenon is that vasoconstriction induced by a low concentration is an insufficient stimulus to promote the EDRF release process, while the endothelium is unable to overwhelm higher concentration-induced vasoconstriction. This notion is supported by the report by Gündüz et al (22) that high intravascular pressure impairs both endothelium-dependent and independent dilation of rat small mesenteric arteries.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, it has been demonstrated that acute and transient high intravascular pressure cause endothelial dysfunction in vessels from normotensive subjects. 25,26 In a previous study we examined vascular dilation responses of SMA from normotensive Wistar rats under progressively increasing intraluminal pressures and we found that increases in intraluminal pressure impair both endothelium-dependent and-independent dilation responses; 27 the results presented herein for normotensive WKY rats are thus in agreement with our earlier report.…”
Section: Discussionsupporting
confidence: 92%
“…Although it has been suggested that acute increases in TMP in MSAs can impair endothelium-dependent and independent vasodilation [2,3], our results in MSVs indicate the opposite. Differences in the protocols used may account for this discrepancy.…”
Section: Discussioncontrasting
confidence: 83%
“…Previous in vitro studies conducted in pressurized small arteries including MSAs have shown that endothelium-dependent vasodilation [2,3,4,5,9,10] evoked by flow- and receptor-selective agonists is significantly reduced with increases of TMP. Endothelium-independent vasodilation induced by the NO donors, SNP or SNAP, were also reduced by TMP elevation [2,3,4,9]. However, in the present study, the lack of acute pressure effects on BK as well as NO donor-evoked vasodilation suggests that in PGF2α-preconstricted MSVs the activity of endothelial NOS and VSM guanylyl cyclase is not altered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation